Evaluate if x = 13 and y = –4.
3(2x + y)
A.
66
B.
90
C.
15
D.
–90

Question

Asked 11/17/2014 7:01:59 PM

Updated 12/27/2014 9:07:56 AM

1 Answer/Comment

Flagged by yeswey [12/27/2014 9:07:08 AM]

s

Question

Asked 11/17/2014 7:01:59 PM

Updated 12/27/2014 9:07:56 AM

1 Answer/Comment

Flagged by yeswey [12/27/2014 9:07:08 AM]

Rating

8

if x = 13 and y = –4.

3(2x + y) = 3[2(13) + (-4)] = 3(26 - 4) = 3(22) = 66

3(2x + y) = 3[2(13) + (-4)] = 3(26 - 4) = 3(22) = 66

Added 12/27/2014 9:07:56 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/27/2014 12:25:09 PM]

The sum of two consecutive even integers is –46.
What are the numbers?
A.
–26 and –20
B.
–22 and –20
C.
–26 and –24
D.
–24 and –22
**Weegy:** The sum of two consecutive even integers is –46. –24 and –22 are the numbers.
(More)

Question

Expert Answered

Updated 11/17/2014 7:17:04 PM

1 Answer/Comment

Please remember to show your calculations, as stated in the rules.

Added 11/17/2014 7:17:04 PM

(3 pt)
Evaluate if c = 3 and d = –4.
2c ÷ d
A.
4b2.gif
B.
4b1.gif
C.
4b4.gif
D.
4b3.gif

Question

Not Answered

Updated 11/18/2014 9:25:21 AM

1 Answer/Comment

Simplify.
–7 + (–3)x + 5 + (–6)x
A.
12 – 9x
B.
–12 – 3x
C.
2 – 3x
D.
–2 – 9x **Weegy:** 7 ? 3x ? 4 + x
= 3 - 2x (More)

Question

Updated 11/17/2014 7:46:41 PM

1 Answer/Comment

–7 + (–3)x + 5 + (–6)x

= -7 - 3x - 6x + 5

= -2 - 9x

= -7 - 3x - 6x + 5

= -2 - 9x

Added 11/17/2014 7:46:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/17/2014 7:51:19 PM]

Evaluate if x = 13 and y = –4.
3(2x + y)
A.
66
B.
90
C.
15
D.
–90 User: =

Question

Not Answered

Updated 11/18/2014 9:26:27 AM

1 Answer/Comment

Simplify.
–9 + (–5)x + 3 + (–2)x
A.
3 – 16x
B.
–6 + 3x
C.
–12 – 7x
D.
–6 – 7x
**Weegy:** –9 + (–5)x + 3 + (–2)x = -9 - 5x + 3 - 2x = -7x - 6 (More)

Question

Updated 11/18/2014 1:32:49 PM

0 Answers/Comments

34,559,042

questions answered

There are no comments.